2017
DOI: 10.1186/s40360-017-0119-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment of clarithromycin at a low concentration improves hydrogen peroxide-induced oxidant/antioxidant imbalance in human small airway epithelial cells by increasing Nrf2 mRNA expression

Abstract: BackgroundClarithromycin (CAM), a representative macrolide antibiotic, has been used widely at low doses for long-term therapy of chronic inflammatory airway diseases. Anti-inflammatory effects of macrolide antibiotics were first discovered in clinical practice. Although oxidative stress is known as a key pathogenesis factor in chronic airway inflammatory diseases, the mechanism of action of low-dose, long-term CAM therapy remains unclear. We aimed to examine the cytoprotective action of CAM against hydrogen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…Lipid peroxidation is also one of the causes of cellular aging, and prevention of lipid peroxidation can delay the aging process. Thus, GSH-Px plays an important role in preventing oxidation and aging (Iwayama et al, 2017). Through enzymatic and nonenzymatic systems, the body produces oxygen free radicals, which can attack polyunsaturated fatty acids in biofilm, trigger lipid peroxidation, and thus form lipid peroxides, such as MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation is also one of the causes of cellular aging, and prevention of lipid peroxidation can delay the aging process. Thus, GSH-Px plays an important role in preventing oxidation and aging (Iwayama et al, 2017). Through enzymatic and nonenzymatic systems, the body produces oxygen free radicals, which can attack polyunsaturated fatty acids in biofilm, trigger lipid peroxidation, and thus form lipid peroxides, such as MDA.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, studies have shown that the enhancer of γ-GCS contains Nrf2 binding sequence and is regulated by Nrf2. Nrf2 are positively correlated with γ-GCS mRNA and protein levels, and the knockout of Nrf2 resulted in the decreased expression of two subunits of γ-GCS in mouse fibroblasts and hepatocytes [ 30 ]. NQO1 is a protective reductase that protects cells from oxidation and aging induced by quinonoid compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a high possibility that anti-apoptotic factors are produced via NF-κB activation [57, 58], thereby enabling necrosis [59]. Also, as reported in the previous study [8], the levels of intracellular CAM gradually changed over time and did not plateau until after 72 h incubation of the cells with CAM. The results showed that cells incubated with 10 μM CAM did not reach concentrations of more than twice that of cells incubated with 5 μM CAM; however, significantly higher intracellular CAM concentrations were observed.…”
Section: Discussionmentioning
confidence: 90%